2017
DOI: 10.3805/eands.9.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various antiepileptic drugs in benign infantile seizures with mild gastroenteritis

Abstract: Purpose: This study sought to deter mine the appr opr iate choice of antiepileptic dr ugs (AEDs) for seizures during the acute phase in patients with benign infantile seizures with mild gastroenteritis (BISMG). Methods: We retrospectively investigated the efficacy and dose of AEDs for BISMG by reviewing the medical records of 42 patients diagnosed with BISMG. In this study, AEDs were regarded as effective when seizures ceased for >24 h after administration. Results: AEDs were administered to 39 of 42 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…81) Similarly, another study showed that 1-day treatment with low-dose carbamazepine was effective for CwG. 82) Some studies demonstrated that fosphenytoin and chloral hydrate are also effective for CwG. 83,84) In addition, a recent study showed that a single dose of lacosamide was well tolerated in patients with CwG.…”
Section: Treatment and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…81) Similarly, another study showed that 1-day treatment with low-dose carbamazepine was effective for CwG. 82) Some studies demonstrated that fosphenytoin and chloral hydrate are also effective for CwG. 83,84) In addition, a recent study showed that a single dose of lacosamide was well tolerated in patients with CwG.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Another study reported that 1-day treatment with carbamazepine or lidocaine effectively treated clustering seizures in CwG [ 81 ]. Similarly, another study showed that 1-day treatment with low-dose carbamazepine was effective for CwG [ 82 ]. Some studies demonstrated that fosphenytoin and chloral hydrate are also effective for CwG [ 83 , 84 ].…”
Section: Treatment and Prognosismentioning
confidence: 99%